1995
DOI: 10.1128/aac.39.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid penetration of amikacin in children with community-acquired bacterial meningitis

Abstract: The penetration of amikacin into the cerebrospinal fluid (CSF) was studied with 16 children (mean age, 1 year and 9 months; range, 4 months to 8 years) with community-acquired bacterial meningitis. Amikacin was given intravenously at a dose of 7.5 mg/kg of body weight twice daily. CSF was collected on day 1, at the expected peak concentration of amikacin in CSF. The mean (standard deviation) concentration of amikacin in CSF was 1.65 (1.6) mg/liter. Concentrations of amikacin in CSF correlated significantly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…Such an approach allowed investigation of amikacin disposition at the anticipated low concentrations. Based on this HPLC method, a median amikacin CSF concentration of 1.08 mg/liter (range, 0.34 to 2.65 mg/liter) was documented in neonates, but the absence of any correlation between markers of CSF inflammation and the T eq are in contrast to other reports in children and adults where CSF amikacin concentrations appear to be increased in the presence of meningitis (7,8,13,24,26,28). We did note a correlation between the amikacin CSF concentration and the CSF protein content (Fig.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Such an approach allowed investigation of amikacin disposition at the anticipated low concentrations. Based on this HPLC method, a median amikacin CSF concentration of 1.08 mg/liter (range, 0.34 to 2.65 mg/liter) was documented in neonates, but the absence of any correlation between markers of CSF inflammation and the T eq are in contrast to other reports in children and adults where CSF amikacin concentrations appear to be increased in the presence of meningitis (7,8,13,24,26,28). We did note a correlation between the amikacin CSF concentration and the CSF protein content (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…Using this WBC threshold (21 cells/mm 3 ) as a dichotomous variable, we were unable to show any significant difference in amikacin CSF concentration in this cohort of neonates (1.16 versus 1.15, P ϭ 0.95). Gaillard et al documented amikacin CSF concentrations in a cohort of 16 children (range, 4 months to 8 years old) with community-acquired bacterial meningitis given intravenous amikacin (7.5-mg/kg twice daily) (13). An inverse correlation with CSF glucose level, but not with the CSF protein concentration or leukocyte count was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study is that we did not investigate cochlear or brain inflammation, but previous studies have shown that AGs do lead to transient inflammatory states (Jiang et al, 2017). Additionally, AGs may cross the blood-labyrinth (Kalinec et al, 2017) and blood-brain barriers in children (Gaillard et al, 1995) and in elderly adults (Mattappalil and Mergenhagen, 2014). Thus, future animal studies might refine the doses and compare different AGs to further detail the otoprotective effects of ebselen on ototoxin-induced cochlear inflammation.…”
Section: Temporary Threshold Shifts In the Absence Of Detectable Hairmentioning
confidence: 99%
“…The concentrations of aminoglycosides achieved in the CSF as a result are variable (Lutsar et al, 1998), but appear to be sufficiently high for excellent therapeutic results (Gaillard et al, 1995). While the highly polar nature of aminoglycosides suggests that they would not be able to cross the blood-brain barrier, and this is usually the case, this membrane is compromised and more permeable when inflammed in bacterial meningitis.…”
Section: Bioavailabilitymentioning
confidence: 99%